Anticorrosive Effects of Some Thiophene Derivatives Against the Corrosion of Iron: A Computational Study - Guo, Lei; Safi, Zaki S.; Kaya, Savas; Shi, Wei; Tüzün, Burak; Altunay, Nail; Kaya, Cemal (Frontiers in Chemistry, 2018)
It is known that iron is one of the most widely used metals in industrial production. In this work, the inhibition performances of three thiophene derivatives on the corrosion of iron were investigated in the light of several theoretical approaches. In the section including DFT calculations, several global reactivity descriptors such as EHOMO, ELUMO, ionization energy (I), electron affinity (A), HOMO-LUMO energy gap (ΔE), chemical hardness (η), softness (σ), as well as local reactivity descriptors like Fukui indices, local softness, and local electrophilicity were considered and discussed. The adsorption behaviors of considered thiophene derivatives on Fe(110) surface were investigated using molecular dynamics simulation approach. To determine the most active corrosion inhibitor among studied thiophene derivatives, we used the principle component analysis (PCA) and agglomerative hierarchical cluster analysis (AHCA). Accordingly, all data obtained using various theoretical calculation techniques are consistent with experiments.